The optimal industry structure in a vertically related market - Raffaele Fiocco (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2010)
We consider a vertically related market characterized by downstream imperfect competition and by the monopolistic provision of an essential facility-based input, whose price is set by a social-welfare maximizing regulator. Our model shows that the regulatory knowledge about the cost for providing the monopolistic input crucially affects the design of the optimal industry structure. In particular, we compare ownership separation, which prevents a single company from having the control of both upstream and downstream operations, and legal separation, under which these activities are legally unbundled but common ownership is allowed. As long as the regulator has full information, the two industry patterns yield the same social welfare level. However, under asymmetric information about the input costs legal separation can make the whole society better off.
Keywords: D82; L11; L51; 330; access charge; legal separation; ownership separation; regulation; Netzzugang; Lieferanten-Kunden-Beziehung; Marktstruktur; Regulierung; Asymmetrische Information; Eigentümerstruktur; Soziale Wohlfahrtsfunktion; Theorie